The action of physiological and synthetic steroids on the calcium channel CatSper in human sperm - Wehrli, Lydia; Galdadas, Ioannis; Voirol, Lionel; Smieško, Martin; Cambet, Yves; Jaquet, Vincent; Guerrier, Stéphane; Gervasio, Francesco Luigi; Nef, Serge; Rahban, Rita (Frontiers in Cell and Developmental Biology, 2023)
The sperm-specific channel CatSper (cation channel of sperm) controls the intracellular Ca 2+ concentration ([Ca 2+ ]i) and plays an essential role in sperm function. It is mainly activated by the steroid progesterone (P4) but is also promiscuously activated by a wide range of synthetic and physiological compounds. These compounds include diverse steroids whose action on the channel is so far still controversial. To investigate the effect of these compounds on CatSper and sperm function, we developed a high-throughput-screening (HTS) assay to measure changes in [Ca 2+ ]i in human sperm and screened 1,280 approved and off-patent drugs including 90 steroids from the Prestwick chemical library. More than half of the steroids tested (53%) induced an increase in [Ca 2+ ]i and reduced the P4-induced Ca 2+ influx in human sperm in a dose-dependent manner. Ten of the most potent steroids (activating and P4-inhibiting) were selected for a detailed analysis of their action on CatSper and their ability to act on sperm acrosome reaction (AR) and penetration in viscous media. We found that these steroids show an inhibitory effect on P4 but not on prostaglandin E1-induced CatSper activation, suggesting that they compete for the same binding site as P4. Pregnenolone, dydrogesterone, epiandrosterone, nandrolone, and dehydroepiandrosterone acetate (DHEA) were found to activate CatSper at physiologically relevant concentrations within the nanomolar range. Like P4, most tested steroids did not significantly affect the AR while stanozolol and estropipate slightly increased sperm penetration into viscous medium. Furthermore, using a hybrid approach integrating pharmacophore analysis and statistical modelling, we were able to screen in silico for steroids that can activate the channel and define the physicochemical and structural properties required for a steroid to exhibit agonist activity against CatSper. Overall, our results indicate that not only physiological but also synthetic steroids can modulate the activity of CatSper with varying potency and if bound to CatSper prior to P4, could impair the timely CatSper activation necessary for proper fertilization to occur.